(untitled) (SAARC Journal of Agriculture, 2017)
Agricultural development cannot be understood without the use of modern technologies like Information and Communication Technologies (ICTs). The recent developments in ICTs offer a unique opportunity to bring the production enhancing tools and technologies to the growers with much cost effective manner. Worldwide, many studies were published on the role of application of ICTs in agricultural production. However, only a few studies were carried out to know the impact of ICT based service delivery system on agricultural production aspects in Bangladesh. Therefore an attempt has been made to find the impact of ICTs on agricultural production, especially in the food crops. Using a randomised survey with a questionnaire, interviews and focus group discussion, a study was carried out with a sample of 1990 farmers from a population comprises farmers all over the country. The findings from the study after counterfactual analysis and difference in differences analysis as well showed that with the application and use of ICTs, agricultural production was accelerated which was evident from the degree of increase of ICT to that of counterfactual is 0.49 and proved that the Boro rice production from the ICT based service area has increased more than that of non-ICT based area. SAARC J. Agri., 14(2): 78-89 (2016)